Mesenchymal Stromal Cells Overexpressing Farnesoid X Receptor Exert Cardioprotective Effects Against Acute Ischemic Heart Injury by Binding Endogenous Bile Acids. Issue 24 (3rd July 2022) - Xia, Yunlong; Xu, Xinyue; Guo, Yongzhen; Lin, Chen; Xu, Xiaoming; Zhang, Fuyang; Fan, Miaomiao; Qi, Tingting; Li, Congye; Hu, Guangyu; Peng, Lu; Wang, Shan; et al.
Abstract: Bile acid metabolites have been increasingly recognized as pleiotropic signaling molecules that regulate cardiovascular functions, but their role in mesenchymal stromal cells (MSC)‐based therapy has never been investigated. It is found that overexpression of farnesoid X receptor (FXR), a main receptor for bile acids, improves the retention and cardioprotection of adipose tissue‐derived MSC (ADSC) administered by intramyocardial injection in mice with myocardial infarction (MI), which shows enhanced antiapoptotic, proangiogenic, and antifibrotic effects. RNA sequencing, LC‐MS/MS, and loss‐of‐function studies reveal that FXR overexpression promotes ADSC paracrine angiogenesis via Angptl4. FXR overexpression improves ADSC survival in vivo but fails in vitro. By performing bile acid‐targeted metabolomics using ischemic heart tissue, 19 bile acids are identified. Among them, cholic acid and deoxycholic acid significantly increase Angptl4 secretion from ADSC overexpressing FXR and further improve their proangiogenic capability. Moreover, ADSC overexpressing FXR shows significantly lower apoptosis by upregulating Nqo‐1 expression only in the presence of FXR ligands. Retinoid X receptor α is identified as a coactivator of FXR. It is first demonstrated that there is a bile acid pool in the myocardial microenvironment. Targeting the bile acid‐FXR axis may be a novel strategy for improving the curative effect of MSC‐based therapy for MI. Abstract : Adipose tissue‐derived MSC (ADSC) overexpressing farnesoid X receptor (FXR) are intramyocardially injected into the peri‐infarct area after myocardial infarction (MI) and respond to bile acids present in the myocardial microenvironment. Bile acid‐FXR axis activation improves the cardioprotection of ADSC via Angptl4‐mediated paracrine angiogenesis and Nqo‐1‐mediated survival. FXR activaton directly upregulates Angptl4 and Nqo‐1 expression by forming a heterodimer with RXRα.